Bird Flu consultation. The research community's response to Avian Influenza, with special reference to the needs of developing countries - International Livestock Research Institute (International Livestock Research Institute, 2014)
The CD starts with introduction by ILRI Director General Carlos Sere Then follows the seven interviews conducted by Brian Perry, ILRI Epidemiologist covering aspects and issues of the current Avian Flu situation, their experiences, national and regional surveillance as well as community surveillance and action. The representatives were from South East Asia (Robyn Alders, IRPC/KYEEMA Foundation; India (Santanu Bandopadhyay, Ministry of Agriculture; Nigeria (Daniel F Adene, Poultry Diseases Unit, Department of Veterinary Medicine, University of Ibadan; Senegal (Poultry specialist E. Fallou Gueye ISRA/Family Poultry Network; Kenya (Catherine Wanjohi from Department of Veterinary Services); World Bank Adam lagerstedt; and South Africa (Celia Abolnik Ondeistepoort Veterinary Institute, Pretoria). The South East Asia representative talked about Laos, East Tumor. She states that Laos is one of the first countries to suffer the Bird Flu outbreak, which was in 2004. That it has small commercial industry and that people preferred village poultry. The outbreak was limited to commercial units, and that it was under control. The government's key efforts were also discussed. She indicated that in Laos no veterinarians are trained. There is luck of sufficient information and communication. Laos is still building capacity. Surveillance is one of the failures because of neglected veterinary services and education on basic sciences over many years. Community action was also discussed. The interview with India's representative started with geographical distribution of Bird Flu, and limitation to specific areas. It was indicated that it was a sudden outbreak in a district in a remote area commercial farm. Soon after, there was another outbreak in rural backyard poultries. The discussion included developing of national policies, and whom it involved. Other topics were - active laboratories, vaccination, strains imported, compensation to farmers on destroyed birds, depopulation, animal welfare, public health issues, mortalities, and ...